Linking reward processing to behavioral output: motor and motivational integration in the primate subthalamic nucleus - Espinosa-Parrilla, Juan-Francisco; Baunez, Christelle; APICELLA, Paul (Frontiers in Computational Neuroscience, 2013)
The expectation and detection of motivationally relevant events is a major determinant of goal-directed behavior and there is a strong interest in the contribution of basal ganglia in the integration of motivational processes into behavioral output. Recent research has focused on the role of the subthalamic nucleus (STN) in the motivational control of action, but it remains to be determined how information about reward is encoded in this nucleus. We recorded the activity of single neurons in the STN of two behaving monkeys to examine whether activity was influenced by the delivery of reward in an instrumental task, a Pavlovian stimulus-reward association, or outside of a task context. We confirmed preliminary findings indicating that STN neurons were sensitive not only to rewards obtained during task performance, but also to the expectation of reward when its delivery was delayed in time. Most of the modulations at the onset of reaching movement were combined with modulations following reward delivery, suggesting the convergence of signals related to the animal’s movement and its outcome in the same neurons. Some neurons were also influenced by the visuomotor contingencies of the task, i.e., target location and/or movement direction. In addition, modulations were observed under conditions where reward delivery was not contingent on an instrumental response, even in the absence of a reward predictive cue. Taken as a whole, these results demonstrate a potential contribution of the STN to motivational control of behavior in the non-human primate, although problems in distinguishing neuronal signals related to reward from those related to motor behavior should be considered. Characterizing the specificity of reward processing in the STN remains challenging and could have important implications for understanding the influence of this key component of basal ganglia circuitry on emotional and motivated behaviors under normal and pathological conditions.